SOFI/Substrate integrity testing for cryogenic propellant tanks at extreme thermal gradient conditions. Issue 1 (November 2015) - Haynes, M; Fabian, P
Abstract: Liquid propellant tank insulation for space flight requires low weight as well as high insulation factors. Use of Spray-On Foam Insulation (SOFI) is an accepted, cost effective technique for insulating a single wall cryogenic propellant tank and has been used extensively throughout the aerospace industry. Determining the bond integrity of the SOFI to the metallic substrate as well as its ability to withstand the in-service strains, both mechanical and thermal, is critical to the longevity of the insulation. This determination has previously been performed using highly volatile, explosive cryogens, which increases the test costs enormously, as well as greatly increasing the risk to both equipment and personnel. CTD has developed a new test system, based on a previous NASA test that simulates the mechanical and thermal strains associated with filling a large fuel tank with a cryogen. The test enables a relatively small SOFI/substrate sample to be monitored for any deformations, delaminations, or disjunctures during the cooling and mechanical straining process of the substrate, and enables the concurrent application of thermal and physical strains to two specimens at the same time. The thermal strains are applied by cooling the substrate to the desired cryogen temperature (from 4 K to 250 K) while maintaining the outside surface of the SOFI foam at ambient conditions. Multiple temperature monitoring points are exercised to ensure even cooling across the substrate, while at the same time, surface temperatures of the SOFI can be monitored to determine the heat flow. The system also allows for direct measurement of the strains in the substrate during the test. The test system as well as test data from testing at 20 K, for liquid Hydrogen simulation, will be discussed.